Alcohol Use and Human Immunodeficiency Virus (HIV) Infection: Current Knowledge, Implications, and Future Directions. (22nd September 2016) - Williams, Emily C.; Hahn, Judith A.; Saitz, Richard; Bryant, Kendall; Lira, Marlene C.; Samet, Jeffrey H.
Abstract : Alcohol use is common among people living with human immunodeficiency virus (HIV). In this narrative review, we describe literature regarding alcohol's impact on transmission, care, coinfections, and comorbidities that are common among people living with HIV (PLWH), as well as literature regarding interventions to address alcohol use and its influences among PLWH. This narrative review identifies alcohol use as a risk factor for HIV transmission, as well as a factor impacting the clinical manifestations and management of HIV. Alcohol use appears to have additive and potentially synergistic effects on common HIV‐related comorbidities. We find that interventions to modify drinking and improve HIV‐related risks and outcomes have had limited success to date, and we recommend research in several areas. Consistent with Office of AIDS Research/National Institutes of Health priorities, we suggest research to better understand how and at what levels alcohol influences comorbid conditions among PLWH, to elucidate the mechanisms by which alcohol use is impacting comorbidities, and to understand whether decreases in alcohol use improve HIV‐relevant outcomes. This should include studies regarding whether state‐of‐the‐art medications used to treat common coinfections are safe for PLWH who drink alcohol. We recommend that future research among PLWH include validated self‐report measures of alcohol use and/or biological measurements, ideally both. Additionally, subgroup variation in associations should be identified to ensure that the risks of particularly vulnerable populations are understood. This body of research should serve as a foundation for a next generation of intervention studies to address alcohol use from transmission to treatment of HIV. Intervention studies should inform implementation efforts to improve provision of alcohol‐related interventions and treatments for PLWH in healthcare settings. By making further progress on understanding how alcohol use affects PLWH in the era of HIV as a chronic condition, this research should inform how we can mitigate transmission, achieve viral suppression, and avoid exacerbating common comorbidities of HIV and alcohol use and make progress toward the 90‐90‐90 goals for engagement in the HIV treatment cascade. Abstract : This narrative review finds that alcohol use is associated with HIV acquisition and transmission, lack of viral suppression, common comorbid conditions (e.g., hepatitis C, tuberculosis, cardiovascular disease, frailty/falls, depression, trauma, and other substance use disorders), and ultimately mortality among people living with HIV (PLWH). Associations between alcohol use and HIV‐related care and outcomes may disproportionately affect vulnerable subgroups of PLWH. Interventions to address drinking and subsequently improve HIV‐related risks and outcomes have been tested with limited success to date.